2004
DOI: 10.1073/pnas.0404380101
|View full text |Cite
|
Sign up to set email alerts
|

Coding single-nucleotide polymorphisms associated with complex vs. Mendelian disease: Evolutionary evidence for differences in molecular effects

Abstract: Most Mendelian diseases studied to date arise from mutations that lead to a single amino acid change in an encoded protein. An increasing number of complex diseases have also been associated with amino acid-changing single-nucleotide polymorphisms (coding SNPs, cSNPs), suggesting potential similarities between Mendelian and complex diseases at the molecular level. Here, we use two different evolutionary analyses to compare Mendelian and complex disease-associated cSNPs. In the first, we estimate the likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
209
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(218 citation statements)
references
References 24 publications
(30 reference statements)
5
209
0
1
Order By: Relevance
“…Alternative strategies to identify potentially functional genetic variants are therefore clearly needed. Because speciation involves phenotypic divergence in adaptive, usually complex, traits it is tempting to hypothesize that the genetic changes during speciation should involve loci that remain to control phenotypic variation in the relevant phenotypes within the newly emerged species (Thomas and Kejariwal 2004). Next to the obvious implications for evolutionary genetics, this assumption opens up the intriguing possibility of ascertaining the genetic basis of phenotypic variation in humans from a comparative genomic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative strategies to identify potentially functional genetic variants are therefore clearly needed. Because speciation involves phenotypic divergence in adaptive, usually complex, traits it is tempting to hypothesize that the genetic changes during speciation should involve loci that remain to control phenotypic variation in the relevant phenotypes within the newly emerged species (Thomas and Kejariwal 2004). Next to the obvious implications for evolutionary genetics, this assumption opens up the intriguing possibility of ascertaining the genetic basis of phenotypic variation in humans from a comparative genomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Deleterious mutations tend to be localized at conserved protein residues Arbiza et al 2006;Miller and Kumar 2001). More interestingly, a comparison of genes involved in ''normal'' genetic variation, Mendelian disease and complex disorders showed that genes involved in complex traits exhibit a higher rate of protein evolution (Thomas and Kejariwal 2004). Apparently, genes involved in the adaptive evolution of our species are more likely to harbor functional polymorphisms that affect variation in complex traits between humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homology searches are also performed to determine if the substitution is conserved across species. The Panther program analyzes variants and provides subPSEC scores that range from -10 (most severe) to 0 (least severe) (Thomas, et al, 2003;Thomas and Kejariwal, 2004). It then uses a hidden Markov model based on position specific independent counts to convert this data into a probability score that the particular amino acid substitution is damaging.…”
Section: E482mentioning
confidence: 99%
“…(1) Genes, alleles, and haplotypes inferred as being subject to positive selection in humans can be chosen as markers to evaluate their potential associations with the risk of psychotic-affective or other polygenic disorders (Thomas and Kejariwal 2004;Crespi et al 2007). The beauty of this approach is that alleles subject to positive selection are predicted to be functional (McVean and Spencer 2006), which should increase the likelihood that associations will be ascertained (Biswas and Akey 2006).…”
Section: (C) Common Alleles Subject To Positive Selection or Balancinmentioning
confidence: 99%